Analysis of spatio-temporal evolution of droughts in Luanhe River Basin using different drought indices - Kai-yan Wang; Qiong-fang Li; Yong Yang; Ming Zeng; Peng-cheng Li; Jie-xiang Zhang (Water Science and Engineering, 2015)
Based on the monthly precipitation and air temperature from 1960 to 1989 in the Luanhe River Basin, the standardized precipitation evapotranspiration index (SPEI) and standardized precipitation index (SPI) at three- and six-month time scales and the self-calibrating Palmer drought severity index (sc-PDSI) were calculated to evaluate droughts in the study area. Temporal variations of the drought severity from 1960 to 1989 were analyzed and compared based on the results of different drought indices, and some typical drought events were identified. Spatial distributions of the drought severity according to the indices were also plotted and investigated. The results reveal the following: the performances of different drought indices are closely associated with the drought duration and the dominant factors of droughts; the SPEI is more accurate than the SPI when both evaporation and precipitation play important roles in drought events; the drought severity shown by the sc-PDSI is generally milder than the actual drought severity from 1960 to 1989; and the evolution of the droughts is usually delayed according to the sc-PDSI. This study provides valuable references for building drought early warning and mitigation systems in the Luanhe River Basin.